Correlation of dietary intake and physical activity with nutritional status, body composition and hand grip strength in elderly - Etisa Adi Murbawani; Hertanto Wahyu Subagio; Niken Puruhita; Enny Probosari; Aryu Candra (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
ABSTRACT Background: Increased life expectancy has both positive and negative impacts. Elderly group are prone to nutritional issues and body function disorder such as sarcopenia. Factors including dietary intake and physical activity are contributors of sarcopenia.Objectives: The purpose of this study is to analyze the correlation of dietary intake and physical activity with nutritional status, body composition and hand grip strength (HGS) in elderly.Materials and Methods: The study was held on July-October 2020 at the Panti Wredha Dharma Bakti Surakarta. This was a cross-sectional study of 54 elderly subjects. Subjects were selected by purposive sampling method. The data included height was measured using microtoise, while weight and body composition was measured using Bioelectrical Impedance Analyzer (BIA). Dietary intake was obtained through comstock observation. Physical activity was measured by the International Physical Activity Questionnaire. Hand grip strength values was measured by hand grip dynamometer. Data normality analyzed by Kolmogorov-Smirnov test. Bivariate test analyzed by Rank Spearman test.Results: Energy, carbohydrate and fat intake had no correlation with nutritional status, total body fat percentage, subcutaneous fat percentage and skeletal muscle mass percentage (p value > 0.05), but there was a relationship between energy (p value = 0.33), carbohydrate (p value = 0.016) and fat intake (p value = 0.047) with visceral fat percentage. Physical activity had relation with nutritional status (p = 0.048) but had no relationship with total body fat percentage, visceral fat percentage, subcutaneous fat percentage and skeletal muscle mass percentage. Protein intake also had no relationship with HGS value (p value> 0.05).Conclusions: Dietary intake only correlated with visceral fat percentage, but had no correlation with other body composition parameters. Physical activity correlated with nutritional status, but had no correlation with all of body composition parameters. Protein intake also had no correlation with HGS.